Diosgenin Protects Against Kidney Injury and Mitochondrial Apoptosis Induced by 3‐MCPD Through the Regulation of ER Stress, Ca2+ Homeostasis, and Bcl2 Expression. Issue 15 (21st June 2021) - Zhong, Yujie; Jin, Chengni; Han, Jiahui; Zhu, Jiachang; Liu, Qi; Sun, Dianjun; Xia, Xiaodong; Zhang, Yu; Peng, Xiaoli
Abstract : Scope: Diosgenin (DIO) is a natural steroid sapogenin presented in various plants. It exerts anti‐oxidant, anti‐inflammatory and anti‐diabetic nephropathy properties. The present study evaluates the intervention effect of DIO on nephrotoxicity induced by food contaminant 3‐chloro‐1, 2‐propanediol (3‐MCPD) in vivo and in vitro. Methods and Results: Treatment with DIO (15 mg kg −1 d −1 ) in Sprague‐Dawley rats for 4‐week relieves kidney injury induced by 3‐MCPD (30 mg kg −1 d −1 ). In vitro, DIO (2, 6, and 8 µM) alleviates cell injury and apoptosis effectively in human embryonic kidney (HEK293) cells. DIO realizes its protective function via the regulation of endoplasmic reticulum (ER) stress and mitochondrial apoptosis pathway. Blockage of ER stress by 4‐phenylbutyric acid (4‐PBA), a specific ER stress antagonist, inhibits mitochondrial apoptosis, suggesting a connection between mitochondrial apoptosis and ER stress. Furthermore, the study demonstrates that the maintenance of Ca 2+ homeostasis and Bcl2 expression, two main targets of ER stress, contributes to the protection role of DIO on mitochondrial‐dependent apoptosis. In addition, DIO relieves the impairment of oxidative phosphorylation. Conclusion: This study demonstrates that DIO exerts protective effect against kidney injury, mitochondrial dysfunction, and apoptosis through the inhibition of ER stress and the further maintenance of Ca 2+ homeostasis and Bcl2 expression. Abstract : Schematic representation showing that Diosgenin (DIO) protects against kidney injury induced by 3‐chloro‐1, 2‐propanediol (3‐MCPD) through inhibiting ER stress, mitochondrial dysfunction, and apoptosis. Prolonged ER stress can cause mitochondrial apoptosis through regulating Ca 2+ homeostasis and Bcl2 expression after 3‐MCPD treatment. DIO protects against the disorder of Ca 2+ homeostasis and the suppression of Bcl2 expression; thus, mitochondrial apoptosis is inhibited.